(untitled) (Al-Academy, 2023)
The researcher assumes that there is a weakness in the prestige of the state in the contemporary graphic discourse, directed through the channels of digital and printed graphic design. And because the research is of great importance, whether on the theoretical or practical side, the prestige of the graphic discourse of the state and the government is related to the identity and strength of the visual authority of any state, and the feeling of pride, loyalty and belonging to it. The research aims to identify the reality of the state of visual prestige in contemporary graphic discourse. The researcher determined spatially / temporally / objectively by studying the prestige of contemporary graphic discourse in Iraq after the year 2003, and at the level of the three presidencies: the state, the government and the parliament. The theoretical framework dealt with the prestige of man before civilization, while in its second topic it dealt with the prestige of the Mesopotamian civilization, and the third topic dealt with the concept of prestige in contemporary graphic discourse. The researcher did not find previous studies in the field of his research. The methodology, community and research sample were identified, and the selected models were analyzed. The research came out with the most important results: The moral aspect of prestige is not achieved in the graphic discourse of the contemporary Iraqi state. The conclusions were: The state’s prestige is achieved through visible material means in graphic design.